Effectiveness in Bowel Cleansing and Patient Tolerability of Polyethylene Glycol versus Sodium Picosulphate in Patients Undergoing Colonoscopy. (30th May 2020) - Jaiswal, Amit Kumar; Chaudhary, Shatdal
Abstract : Introduction . Colonoscopy is considered as a gold standard investigation for screening of colorectal cancer and other lower gastrointestinal pathologies. Adequate bowel preparation is absolutely necessary for a fruitful colonoscopy. Various bowel cleansing agents are being used for his purpose. The aim of the present study was to compare the two bowel cleansing agents: a single dose of Polyethylene Glycol (PEG) solution and a split dose of Sodium Picosulfate (Na PICOSUL) tablet with regards to cleansing efficacy and tolerability among the patients scheduled for colonoscopy. Methods . It is an open-label hospital-based observational study. A total of sixty-four patients were grouped randomly into two groups of bowel cleansing agents that are PEG and Na PICOSUL during the study period between 1 st December 2015 and 30 th November 2016. Patients' tolerability was evaluated using a structured questionnaire, and the bowel cleansing efficacy was evaluated using the Aronchick Bowel Preparation Scale (ABPS). Results . The group that received PEG solution was found to have better efficacy than that which received Na PICOSUL tablet (63.3% versus 29.4%, respectively, with a P value < 0.028) with excellent grade as per ABPS. The Na PICOSUL group was found better in terms of tolerability than the PEG group as nausea/vomiting was encountered significantly higher in the PEG group than in the Na PICOSUL group (43.3% versus 11.8%, respectively, with a P value < 0.01). Conclusions . Colonic preparation with a split dose of Na PICOSUL tablet was better tolerated than the evening before regimen of PEG solution. However, PEG solution was found to be more efficacious in bowel cleansing, but procedural performance and lesion detection were similar for both agents.